Evaluasi Tata Kelola Teknologi Informasi pada Bank BJB Menggunakan Metode COBIT 5 - Nugraha, M Dody; Oktarina, Tri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze the evaluation of information technology governance at bank bjb using the cobit 5 method. This research uses a quantitative approach. The subjects in this study were employees of Bank BJB Palembang Branch who provided answers to questions in the questionnaire. The object of this research is Bank BJB Palembang Branch itself. data collection in this study includes observation, literature study, interviews, and distributing questionnaires. Samples that represent the population are selected by purposive sampling method, with the condition that the sample truly represents the user. The analysis technique in this study is based on data obtained through questionnaires distributed to several employees of Bank BJB Palembang Branch. From the research results it can be concluded that there is a gap or gap of 0.73 from the gap analysis results. This gap is divided into five domains, namely EDM01 there is no IT risk assessment, IT policies regarding IT governance. EDM02 there is no assurance that IT investment can balance the benefits and the budget spent can be balanced. EDM03 there is no awareness of exposure to IT risks and controls and evaluating the effectiveness of IT risk management monitoring. EDM04 No IT-related strategies and policies for software standards, hardware defined. EDM05 There is no evidence of process objectives in IT governance stakeholders.